Developing Critical Thinking in EFL through Visible Thinking Routines: Experiences of Teachers in a Chinese International School - Lei, Ying; Joseph Jeyaraj, Joanna (International Journal of English Language Education, 2023)
In recent years, critical thinking (CT) has become a key factor in promoting language learning, especially in Chinese international schools. However, there is limited research about the approaches to develop CT within this context. Therefore, this paper focuses on the ways in which English language teachers engage with Visible Thinking (VT) routines to develop students’ CT ability among students in an international school in Fujian, China. Also covered in this paper are suggestions on how to overcome certain challenges that result from the use of these routines. In this qualitative study, data were obtained through semi-structured interviews with four EFL teachers and data were analysed thematically. The results show that English teachers utilized VT routines as a lead-in and a text-based discuss tool to improve students’ CT skills. Additionally, six challenges were identified and these related to the complexity level of VT routines and teachers’ understanding of the these routines, students’ difficulty in providing critical answers, lack of motivation, internet dependence issues and students’ language proficiency level. To overcome these difficulties, teachers should devote more time to lesson-planning and problem-prediction, recognize the value of content knowledge, encourage motivation through peer-support and reward-systems, encourage discussion. Implications for teaching include gaining familiarity with VT routines which can be done through informal conversations with colleagues and also through professional development activities.